Moderatıng factor of locus of control on the relatıonshıp between leadershıp style and employees motıvatıon - Elhawı, Eman (My University, 2016)
DENETİM ODAĞININ LİDERLİK TİPİ İLE MOTİVASYON ARASINDAKİ ŞARTLI DEĞİŞKEN ETKİSİ Bu çalışmada liderlik tipi ile motivasyon arasında denetim odağının şartlı değişken olup olmadığı araştırılmaktadır. Motivasyon bağımlı liderlik bağımsız değişken ve denetim odağı ise şartşı değişken olarak modele konulmuştur. Literatürede liderlik tipleri ile motivasyon arasındaki ilişki incelenmiştir. Çalışmada faktör analizi ve regreyon analizi kullanılarak ilişki ortaya çıkarılmaya çalışılmıştır. Çalışmada medya sektöründe çalışan 146 çalışandan anket toplanmıştır. Çalışma Laissez-faire ve motivasyon arasında pozitif bir ilişki bulunmuştur. Ancak yeterli sayıda dıştan denetimli çalışan olmadığı için şartlı değişken etkisi test edilememiştir. AnahtarKelimelerLiderlikTipleri, Motivasyon , DenetimOdağı MODERATING FACTOR OF LOCUS OF CONTROL ON THE RELATIONSHIP BETWEEN LEADERSHIP STYLE AND EMPLOYEES MOTIVATION The motivation behind this study was to set up the importance of the Locus in controlling the relation between management style and motivation in media sector. Leadership styles that are transactional, motivational and laissez-faire were treated as the independent variables with the dependent variable being the employee’s motivation. Other researchers have carried out studies on the leadership styles and the notion of employee’s motivation. Nevertheless, the relationship between the investigative Locus of Control (LOC) with other key variables has been left out. Thus, this study gives detailed information about the same. A couple of theories have been used in explaining both the dependent and independent variables which were also reviewed when doing this study. The hypotheses were that a moderating effect of Locus of Control occurs on: (a) the relationship between Transformational Leadership and employee’s motivation. (b) The relationship between Laissez-faire leadership and employee’s motivation.The quantitative statistical approach was used relying on both primary and secondary sources of data which were after that analyzed using the regression analysis. The sources of secondary data comprised mainly of printed documentations and publications relating to the subject matter. Prime data was obtained by using questionnaires which were randomly administered to a sample size of 146 employees. Out of the 130 issued questionnaires, only 96 were received with 50 being filled online by an employee from different gender, age, academic qualification, work status, experience and contact frequency with the manager. Twelve questionnaires for dependent variables and independent variables were used in this study. The locus being both internal and external was analyzed using the Rotter’s dimension personality. The study established a positive relationship between Laissez-faire and the motivation expected among workers. There was an evident positive relationship between transformational relations between the intrinsic motivations of followers. However, there was no clear relationship established between the impact of LOC on the leadership style used and the possible motivation. Some leadership styles have surpassed the rest in their usage with transformation and transactional being mostly used. A further recommendation is put forward for the multiple Rotter’s scale Locus control for an expansive sample size. Leadership Style, Motivation, Locus of Control
Keywords: İşletme; Liderlik; Yönetim